The Effect of Menstrual Hygiene Management on Academic Performance of Adolescents Girls in Zone One Bidibidi Refugee Schools Northern Uganda, Yumbe District, Bidibidi Refugee Settlement. - Magret Akita (Uganda Christian University, 2024)
About 1.8 billion women worldwide are menstruating, with as estimate of about 800 million who lack access to menstrual products and adequate facilities for Menstrual Hygiene Management to effective management. Girls and women within the cycle need easy access to menstrual materials, general information on good practices and above all supportive environment where they can easily manage their menstrual cycles without fear especially the adolescents in terms of water, sanitation and hygiene (WASH) facilities. The aspect of the menstrual management is so sensitive that needed lots of resource to ensure health practice for the better of woman’s body. However, it’s of great concern that about 52% girls and women lack access to health practice of the (MHM) (World Bank 2022) and its worst in the low-income countries where a half of the schools lack adequate water, sanitation and hygiene services which are so crucial and vivid to enable girls and even the female teachers to manage menstruation. (UNICEF 2015). Therefore my aim is to explore the effect of menstrual hygiene management on academic performance of adolescent girls relating on how menstrual management has contributed to the poor academic performance of the adolescent girls in Bidibidi camp. Therefore with basic efforts to create more awareness, information and knowledge on MHM among the adolescent, efforts to ensure better hygienic materials and places and innovative skills on how to use the available materials (Lenia et al 2019). Hence a study to understand the lack of information regarding the menstrual hygiene management among the adolescent leading to their poor academic performance.